Фiтоiндикацiя стану навколишнього природного середовища з використанням електрофiзiологiчних методiв - Чемерис, I.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The questions of the variety of the biological potentials of plants, their origin, properties, and methods of measurement are considered. The dynamics of the electrophysiological data of wheat plants Myronivska-65 under the acidening of soils is investigated, and the correlation between the researched characteristics is determined. The calculated regression equation enables one to predict the expected levels of voltage and resistance for the determined data of soil acidity. The conclusions are made on the reliability of electrophysiological data and the possibility to use the method in the practice of ecology biomonitoring.